(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
In observational research we observe what happens in the real world, and particularly in clinical practice. Contrary to what happens in clinical trials, there is no randomization. While clinical trials are governed by a precise and detailed regulatory framework, for observational research there are no specific regulations (except for the protection of personal data), and reference is made only to guidelines, codes and soft law. Consequently, in the absence of specific regulatory references, ethics committees frequently evaluate observational studies by applying the criteria that apply to clinical trials. This leads to inappropriate weighting and stiffness. To counter the Covid-19 pandemic, measures have been adopted to facilitate research, including observational research. Some provisions are also particularly relevant for information and consent, both for clinical practice and for the protection of personal data. These exceptional measures taken during the pandemic deserve attention: limited to some parts, they could be adopted not only in the emergency context of the pandemic, but also in ordinary situations.